Inmate’s Rehabilitation in Probation and Mediation Service in Lithuanian Penitentiary System - Dermontas, Julius (Acta Paedagogica Vilnensia, 2005)
This article analyses theory and practice of Lithuanian Probation and Mediation service in Penitentiary system. In this article is emphasized that in many world countries, as well as European Union countries, punishment politic is changed in detailed and wise solving personal and social problems of people, instead of imprisonment is widely used alternatives of imprisonment – to leave in community with special sanctions and charges. These ideas reflect in 47 article of Punishment Code (Penitentiary Code, which was initiated in 2002): to help in solving personal and social problems of clients of probation and mediation service (probation and mediation service in Lithuania is named Correctional Inspectorates, but there is no created mediation service and there are no voluntaries confirmed by penitentiary law). In article here is researched the main problems of adults and juvenile clients of correctional inspectorates. The feelings and problems of the juvenile clients of correctional inspectorates are described. It is the main task to help in solving these problems and they would change behaviour. Now in Lithuania there is creating the government conception about probation and mediation, but there is no special act of probation and mediation, there is no mediation service and supervisor service. The researches of this article will help to make•the rehabilitation process quicker in correctional inspectorates.